Covid 19 Fear and Safety Compliance: A Study of Nursing Professionals - Haroon Bakari; Sajid Bashir; Farzana Akmal Memon; Dina Metwally (SAGE Open)
The novel coronavirus COVID-19 pandemic caused a global medical emergency. Nurses working in COVID-19-designated tertiary care hospitals in Pakistan were particularly at risk. It is important to investigate compliance with safety measures among nurses to ensure their safety at the workplace. This study examines the role of fear of COVID-19 in determining compliance with safety measures, with the mediating role of safety consciousness. The data were collected from 722 nurses through a questionnaire using a cross-sectional study design. The results provide new insights into nurses’ safety literature by showing that the fear of COVID-19 and a positive safety climate have led to increased compliance with safety measures among nurses. The study suggests that improving the safety climate and addressing the fear of COVID-19 can enhance safety compliance and make the workplace safer for nurses.